IN VITRO SCREENING OF ZIZIPHUS MAURITIANA AND TERMINALIA ARJUNA FOR THEIR ANTHELMINTIC ACTIVITY - A. Hussain; M. N. Khan; M. S. Sajid; Z. Iqbal; M. K. Khan; R. Z. Abbas; M. A. Raza; E U. Ghafoor; I. Ahmad (Journal of Animal and Plant Sciences, 2011)
The present studies have been planned to evaluate ovicidal efficacy of Ziziphus mauritiana and Terminalia arjuna leaves. For this purpose, egg hatch test (EHT) was conducted on nematode ova to investigate the in vitro ovicidal effects of crude aqueous extract (CAE) and crude aqueous methanolic extracts (CAME) of the leaves of the plants. Lethal concentration 50 (LC50) values of CAE and CAME of Ziziphus mauritiana leaves were 0.1773 and 0.6778 while of Terminalia arjuna leaves were 1.502 and 3.002 respectively. This study shows that Ziziphus mauritiana and Terminalia arjuna leaves possess in vitro anthelmintic activity. The study also suggests further large scale pharmacological and toxicological studies for their use in veterinary medicine.
Keywords: Ziziphus mauritiana; Terminalia arjuna; egg hatch test; Anthelmintic activity; Leaves; Pakistan.